The Relationship between Premature Birth and the Size of Expressive Lexicon in18-36-month-old Children - Mahmood Bijankhan; Hamid Reza Badeli; Afagh Hassanzadeh Rad; Zahra Hassanzadeh rad; Elaheh Nouri; Setila Dalili (Journal of Holistic Nursing and Midwifery)
Introduction: The acquisition of speech and language constitutes a dynamic part of two-year-old children s growth. Expressive lexicon is a key indicator of language ability in these children. Premature birth, birth before gestational week 37, is one of the most common risk factors associated with learning skill development. A review of literature suggests inconsistent results on the relationship between preterm birth and the size of expressive lexicon in children.